Ethics Guidelines for Immersive Journalism - Sánchez Laws, Ana Luisa; Utne, Tormod (Frontiers in Robotics and AI, 2019)
When journalists decide to invite audiences to witness a news event “as if they were there” through immersive journalism, they acquire new responsibilities towards audiences. When audiences accept such an invitation, they also must understand the responsibilities that experiencing the news event with a much higher degree of bodily involvement entails. The main goal of this article is to discuss the elements of ethics guidelines that can address the new ethical challenges brought about by immersive journalism. We wish to investigate ethics guidelines for immersive journalism from two perspectives: existing ethical contexts, insofar as these can be understood from analyzing codes of ethics and press ethics bodies rulings, and journalists’ own ethical concerns when doing immersive journalism. Through an investigation of these perspectives, we wish to propose a set of key elements that can help reshape ethics guidelines so that they better address the issues raised by immersive journalism. We investigate ethics guidelines in a select sample of codes used by organizations currently practicing immersive journalism. Selected organizations include the New York Times, Washington Post, Associated Press, Reuters, Vice News, the Guardian, Al Jazeera, El País, and the regional newspaper Sunnmørsposten in Norway. A thorough discussion of these perspectives will support our proposal for how the audience dimension can be better considered in ethics guidelines for immersive journalism, by a) establishing methods to assess early on how technologies change ethical practice, b) making journalists and press ethics bodies more aware of the audience dimension, including the need to consider the principle of doing no harm as also involving doing no psychological harm to audiences, and c) establishing pathways to include news audiences as partners in the construction of ethics guidelines for immersive journalism.